Risk Factors of COVID-19 Infection Among Health Workers Post-Vaccination in Jakarta - Saputra, Rahmat; Prihartono, Nurhayati Adnan; Sudaryo, Mondastri Korib; Mahkota, Renti; Devita, Yeni; Arisanti, Ni Wayan Deisy (Kesmas, 2024)
One of the best approaches to stop the COVID-19 pandemic is vaccination. In Indonesia, the first round of vaccinations was prioritized for health workers on January 14, 2021 (first dose) and March 1, 2021 (second dose). However, some health workers who have been vaccinated were found to be reinfected after receiving the second dose. This cross-sectional study examined the risk factors for COVID-19 infection among health workers after vaccination using secondary and primary data. The data analysis was carried out in univariate (examining the frequency distribution and proportion of independent variables), bivariate (Chi-square test to explore the relationship between independent and dependent variables), and multivariate (Logistic Regression to assess the strength of the relationship between independent and dependent variables). The results showed that the variables associated with post-vaccination infection included COVID19 infection history (PR: 2.16, p-value <0.05), age (PR: 0.64, p-value <0.05), hypertension (PR: 1.52, p-value <0.05), direct contact with patients (PR: 2.02, p-value <0.05). It is recommended that health workers aged >37 years with a history of diabetes mellitus, hypertension, or previous COVID-19 infection, working directly with patients, and using Personal Protective Equipment level 1 daily should be prioritized for booster vaccinations.